Perlindungan Masyarakat Hukum Adat terhadap Dampak Global Warming di Provinsi Riau - Rika Lestari; Zainul Akmal (Faculty of Law, Universitas Riau, 2021)
The impact of global warming in Indonesia are felt by all people, including the adat law community. Because the community is live from nature who manage natural resources for daily needs. It also happens in Riau Province. The purpose of this study is to determine the protection of adat law community to the impact of global warming in Riau Province. This is socio-legal research by using primary and secondary data. The results show that the impact of global warming on the adat law community in Riau Province is real and widespread in various aspects of life, such as prolonged ecological disasters, floods, land fires, and droughts; Climate change causes unpredictable seasons, the community is unable to predict planting times according to the seasonal calendar has been passed down for generations, causing crop failure; Community needs additional capital to manage agricultural land to adapt the climate change, they need synthetic fertilizers, pesticides, herbicides, and others. Even though formerly, additional treatments are not necessary; Forest and land fires cause a smog disaster, the haze impact make the loss of honey bees from the sialang trees, so reduced honey production. the conclusion is that the impact of global warming decreases standard life, economic, health, and environmental. Therefore, the government have to control the impact of global warming which is extracted from the values of local wisdom that live and develop in the adat law community, especially in Riau Province in terms of managing existing natural resources. Keywords: Dampak, Global Warming, Masyarakat Hukum Adat, Provinsi Riau